The The Correlation between Vocabulary Mastery and Reading Comprehension among High School Students - Ofayani, Desi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
Exploring students background knowledge in pre-reading activities suggests the importance of interaction in the process of meaning making which requires appropriate vocabulary. Although many factors constitute students’ comprehension, vocabulary should be the main concern in EFL reading classes. Consistence with this premise, the current study was aimed at proving the correlation between students’ vocabulary mastery and their reading comprehension at tenth grade students of SMAN 1 Kramatwatu. This correlational study involved 37 students taken through purposive random sampling. Vocabulary and reading tests were employed to determine the correlation between students’ vocabulary mastery and their reading comprehension. Based on the results of the research, it could be noticed that the R-count > R-table (0.357 > 0.324) which means that H0 was rejected and H1 was accepted. In conclusion, there was a low correlation between vocabulary mastery and reading comprehension at tenth grade students of SMAN 1 Kramatwatu.